Molecular Mechanics and Quantum Chemistry Based Study of Nickel-N-Allyl Urea and N-Allyl Thiourea Complexes - P. D. Sharma; Shruti Srivastava; P. P. Singh (E-Journal of Chemistry)
Eigenvalue, eigenvector and overlap matrix of nickel halide complex of N-allyl urea and N-allyl thiourea have been evaluated. Our results indicate that ligand field parameters (Dq, B’ and β) evaluated earlier by electronic spectra are very close to values evaluated with the help of eigenvalues and eigenvectors. Eigenvector analysis and population analysis shows that in bonding 4s, 4p, and 3dx2-y2, 3dyz orbitals of nickel are involved but the coefficient values differ in different complexes. Out of 4px, 4py, 4pz the involvement of either 4pz or 4py, is noticeable. The theoretically evaluated positions of infrared bands indicate that N-allyl urea is coordinated to nickel through its oxygen and N-allyl thiourea is coordinated to nickel through its sulphur which is in conformity with the experimental results.